A new cuspidate ptychodontid shark (Chondrichthyes; Elasmobranchii), from the Upper Cretaceous of Morocco with comments on tooth functionalities and replacement patterns. (March 2022) - Amadori, Manuel; Kindlimann, René; Fornaciari, Eliana; Giusberti, Luca; Kriwet, Jürgen
Abstract: The first articulated dentition of † Ptychodus from Africa is described herein. The specimen, likely coming from the Turonian of the Asfla area (Goulmima region, southeastern Morocco), exhibits a well-preserved lower dental plate of a second-level predator. A new species, † P. maghrebianus sp. nov., is erected herein based on this durophagous dentition characterised by imbricated cuspidate teeth. We employed for the first time in † Ptychodus multiple quantitative analyses and statistical parametric and non-parametric tests to process biometrical data taken from articulated, associated and isolated teeth. The quantitative approach (morphospace analysis) is exploited herein to support the traditional taxonomic identification (qualitative examination) of † P. maghrebianus sp. nov. and to separate it from the similar cuspidate species, † P. mortoni . Morphospace reconstructions confirm a marked lower dental heterodonty (mesio-distal patterns) for both species. The analysis protocol employed here also allows assigning indeterminate teeth as belonging to † P. mortoni . The reconstruction of the entire lower dental plate of † P. maghrebianus sp. nov. shows a cuspidate dentition probably able to reduce tooth damages when crushing thin-shelled prey. Both dental morphologies and tooth wear patterns suggest a peculiar food processing and a diet mainly consisting of bivalves, decapods and small fish for this durophagous predator. Trophic reconstructions of the Turonian ichthyofauna inhabiting the middle to outer ramp environment of the Asfla area emphasize that † P. maghrebianus sp. nov. and the batoid † Tingitanius most likely represented second-level consumers, whereas the sclerorhynchiforms † Asflapristis and † Ptychotrygon represented third-level predators. Top positions within the food web were occupied by larger predaceous elasmobranchs (e.g., † Squalicorax ). Highlights: Description of the first articulated dentition of † Ptychodus from Africa. Establishment of the new Moroccan species, † P. maghrebianus. Identification of cuspidate Ptychodus species based on multiple statistical analyses. A peculiar food processing hypothesized for the durophagous † P. maghrebianus. Trophic reconstructions of the Turonian ichthyofauna from the Asfla area (Morocco).